Materials corrosion and protection - Huang, Yongchang (Writer on corrosion); Zhang, Jianqi (Writer on corrosion) (Shanghai Jiao Tong University Press ; Walter de Gruyter, GmbH, 2018)
This book introduces corrosion mechanisms and protection technologies for metallic and non-metallic materials. A focus lies on the protection of high-tech materials with applications in space and environments exposed to unclear radiation and biological hazards. The determination, measurement and control of different corrosion mechanisms are discussed in detail. Combining theories with case studies, it is an essential reference for material scientists and engineers.